(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2021)
The ordinary Portland cement (OPC) industry is an energy-intensive industry that causes many environmental problems. Such as air pollution due to carbon dioxide CO2 emission to the atmosphere, which contribute global warming phenomena. The OPC industry is responsible for 7% of CO2 emitted into the air. With the expectations of producing billions of tons of OPC to keep pace with the growing movement in the construction sector, many attempts have appeared in recent years by researchers to explore cement alternatives that are effective and environmentally friendly, hence the term green concrete. Different types of waste materials resulting from the manufacturing or construction processes can considered as recyclable materials that can be used as a partial or full replacement of OPC and the other concrete components (coarse aggregates- fine aggregates-water) to produce green concrete. This will reduce the harmful environmental impact resulting from the cement industry, reduce energy consumption, help to solve the problem of disposal of these wastes, and preserving the natural resources for a longer time. The current paper first discusses the positive impacts of using alternative waste materials in green concrete production. As well as a review of the latest findings of the previous studies related to the production of green concrete and the use of recycled waste materials in different forms in concrete. while giving a more concentrating view of the latest developments in this field in Saudi Arabia. The findings presented through this review seek to provide a deeper understanding of the process of producing and executing the green concrete in an attempt to reduce the gap between the scientific research results that have become popular among researchers, and the practical side that has not yet reached the level of ambitions in this field.